PENGARUH KINERJA PEGAWAI, KOMITMEN ORGANISASI , SISTEM PENGENDALIAN INTERN PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA, PENGAWASAN FUNGSIONAL DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Lingga) - Sufiani Sufiani; Taufik Taufeni; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The study aimed to examine the effect of : (1) Performance Employee,(2) Commitment Organization, (3) Government Internal Control System, (4)Humam Resources Competencies, (5) Functional Control, (6) Region’s FinancialAccounting System of the Effectiveness of Financial Management. The populationin this study were employed who worked in the OPD Lingga District (23government agencies). The sampling method used in this study is purposivesampling method. The respondent inthis study is the head of OPD, the head offinancial, treasure of OPD and financial records staff / accounting. the analyticalmethod used is multiple regression analysis using the program StastisticalProduct and Service Solution (SPSS) version 23.0. The results of this studyindicate that: (1) performance employee has a effect on effectiveness of financialmanagement area with a significant level of 0.001 <0.05, (2) commitmentorganization has a effect on effectiveness of financial management area with asignificant level of 0.001<0.05, (3) government internal control system has aeffect on effect on effectiveness of financial management area with a significantlevel of 0.047 <0.05, (4) humam resources competencies has a effect oneffectiveness of financial management area with a significant level of 0.024<0.05, (5) functional control has a effect on effectiveness of financialmanagement area with a significant level of 0.000<0.05, (6) region’s financialaccounting system has a effect on effectiveness of financial management area witha significant level of 312>0.05.Keywords : Employee, Commitment, Internal Control, Competenc, FungctionalControl, Financial Accounting and Effectiveness